Konsepsi tentang Tajdīd dalam Menjawab Tantangan Globalisasi Perspektif M. Quraish Shihab - Aisma Maulasa; Zulkarnain Suleman (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2019)
This article aims to elaborates M. Quraish Shihab's thoughts on the concept of tajdīd in addressing the challenges of globalization. In conducting legal reasoning, M. Quraish Shihab distinguishes between principles and particulars (al-qat’ī min al-zannī), understanding the legal sources contextually and allegorically. M. Quraish Shihab's legal response in fatwas based on the moderation paradigm, ease and far from being fanaticism. It is very frequently happening that the choice and answer to the law and the fatwa of M. Quraish Shihab opposite the mainstream, such as the ability to choose a leader who is not a religious leader congratulates Christians on the Christmas day and does not require a headscarf. For these different opinions, liberal accusations are often pinned to M. Quraish Shihab.